2014
DOI: 10.1002/lt.24020
|View full text |Cite
|
Sign up to set email alerts
|

Rho‐kinase inhibitor targeting the liver prevents ischemia/reperfusion injury in the steatotic liver without major systemic adversity in rats

Abstract: Rho-kinase (ROCK) inhibitors improve liver blood flow after ischemia/reperfusion (IR) injury, especially in the setting of steatosis, by decreasing the resistance of intrahepatic microcirculation through hepatic stellate cell (HSC) relaxation. However, the systemic administration of ROCK inhibitors causes severe hypotension; therefore, liver-specific ROCK inhibition is required. Here, we tested vitamin A (VA)-coupled liposomes carrying the ROCK inhibitor Y-27632 for targeted HSCs in steatotic rats. Rat livers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Resolvin D1, which is an endogenous pro-resolving lipid mediator, was reported to polarizing macrophage to M2 phenotype and inhibit liver IRI [20]. ROCK inhibitors were showed a protective effect in liver IRI in the previous study [44,45]. But they thought that effect is hepatic stellate cell dependent.…”
Section: Discussionmentioning
confidence: 97%
“…Resolvin D1, which is an endogenous pro-resolving lipid mediator, was reported to polarizing macrophage to M2 phenotype and inhibit liver IRI [20]. ROCK inhibitors were showed a protective effect in liver IRI in the previous study [44,45]. But they thought that effect is hepatic stellate cell dependent.…”
Section: Discussionmentioning
confidence: 97%
“…We also evaluated the effects of systemic administration of Y‐27632 (10 mg/kg) on ischemia–reperfusion injury in rats and found that this compound improved postoperative liver function and survival rate, but induced a dramatic decrease in blood pressure, supporting that high systemic doses of ROCK inhibitors were necessary for improvement of liver fibrosis and could result in systemic adverse effects, such as hypotension. Therefore, we developed a new DDS, VA‐Lip‐Y, and showed that VA‐Lip‐Y mitigated ischemia–reperfusion injury in the steatotic liver and reduced major systemic adverse effects, such as hypotension . Similarly, in this study, VA‐Lip‐Y treatment suppressed liver fibrosis at a dose of 0.2 mg/kg ROCK inhibitor.…”
Section: Discussionsupporting
confidence: 52%
“…A VA‐coupled liposomal ROCK inhibitor was prepared as previously described . Briefly, empty liposomes (Coatsome EL‐N‐01; NOF, Tokyo, Japan) were prepared to deliver ROCK inhibitor (Y‐27632 [Y]; Wako, Osaka, Japan), and 25 mg empty liposomes were added to 400 μL Y solution (15 mg/mL in phosphate‐buffered saline [PBS]; liposomes carrying Y‐27632 [Lip‐Y]).…”
Section: Methodsmentioning
confidence: 99%
“…New biomarkers including miRNAs may help in predicting risk for PNF. Lastly, recent preclinical research suggests Rho‐kinase inhibitor treatment to prevent extensive ischaemia‐reperfusion injury in steatotic allografts without major systemic adversity thus broadening the horizon of pharmacological interventions in the use of fatty liver allografts …”
Section: Discussionmentioning
confidence: 99%